Analysis Study of Overcurrent Relay in the Underground Distribution Network System in the Business Area of Manado City - Leony Ariesta Wenno; Godeliva Ngala; Deitje S. Pongoh (Fakultas Teknik Universitas Pancasila, 2025)
Currently, the distribution network installed in the business area of Manado City still uses medium-voltage overhead lines (SUTM), while an underground cable system (SKTM) has been planned for implementation. To ensure the reliability of the planned underground distribution network, the selection of protection devices is crucial. In addition, there is still a lack of OCR analysis for underground distribution system protection in Manado City. Therefore, this study aims to obtain the settings for the overcurrent relay (OCR) on the underground cable conductors on the low voltage side. The data needed for this study was obtained through direct field surveys and interviews with relevant parties to gather additional information regarding the standards for underground cable construction. Considering the potential increase in load in the future, the calculation of the OCR protective settings was performed by calculating the cross-sectional area of the medium voltage conductors and the current-carrying capacity of the low voltage conductors. As a result, the setting value for the OCR was determined to be 5 Amperes with a Time Multiplier Setting (TMS) of 0.004.